Effects of blended microbial feed additives on performance, meat quality, gut microbiota and metabolism of broilers - Zhou, Luli; Li, Hui; Hou, Guanyu; Hu, Chengjun; Ji, Fengjie; Peng, Weiqi; Zhou, Hanlin; Wang, Dingfa (Frontiers in Nutrition, 2022)
The present study investigated the effects of blend microbial feed additive (BMFA) in diet on performance, meat quality, gut microbiota and metabolism of broilers. In this study 240 seventy-day-old female Wenchang broilers were randomly allocated into four groups with five replicates of 12 broilers each. Broilers in the control group was fed only basal diet (S0), and the other three groups were fed the same basal diet supplemented with 0.2% (S1), 0.4% (S2), or 0.6% (S3) of BMFA, respectively. The trial continued for 54 days. The results showed that broilers in S2 and S3 had lower average daily feed intake (ADFI) compared with S0 and S1 (P < 0.05). However, diet supplementation with BMFA had no significantly influence on the average daily gain (ADG) and the ratio of ADFI to ADG (F/G) (P > 0.05). The highest thigh muscle percentage was observed in S2 (P < 0.05) among all groups. Diet supplementation with BMFA reduced the shear force in both breast and thigh muscles (P < 0.05) of broilers. An increase (P < 0.05) in the total unsaturated fatty acid (USFA), monounsaturated fatty acids (MUFA), and ratio of unsaturated fatty acids to saturated fatty acid (USFA/SFA) in breast muscles was observed in S3 compared with S0. It was found that the S3 had a relatively higher abundance of Lactobacillus (P < 0.001), as well as a lower abundance of the Bacteroides, Rikenellaceae RC9 gut group, Olsenella, Prevotellaceae UCG-001 and Prevotella (P < 0.05) than the S0. Correlation analysis indicated that a total of 17 differential metabolites between the S3 and S0 were significantly correlated with the 7 differential genera microflora. Overall, diet supplementation with 0.6% of BMFA can significantly improve the meat quality of broilers by decreasing the concentration of SFA and enhancing the levels of the total USFA, MUFA and USFA/SFA in breast muscles. Those findings were tightly bound to the higher proportion of Lactobacillus genus in the intestinal tract of broilers influenced by BMFA.